Heterostructured CoO-Co3O4 nanoparticles anchored on nitrogen-doped hollow carbon spheres as cathode catalysts for Li–O2 batteries. Issue 31 (26th July 2019) - Feng, Lixia; Li, Yongliang; Sun, Lingna; Mi, Hongwei; Ren, Xiangzhong; Zhang, Peixin
Abstract : CoO-Co3 O4 nanoparticles coated on nitrogen-doped hollow carbon spheres (N-HC@CoO-Co3 O4 ) are prepared by a simple method, and N-HC@CoO-Co3 O4 when used as the cathode material for a lithium–oxygen battery shows high catalytic performance. Abstract : Lithium–oxygen batteries have received extensive attention due to their high theoretical energy density and environmental friendliness. Herein, CoO-Co3 O4 nanoparticles coated on nitrogen-doped hollow carbon spheres (N-HC@CoO-Co3 O4 ) are prepared by a simple method, and N-HC@CoO-Co3 O4 when used as the cathode material for a lithium–oxygen battery shows high catalytic performance. The nitrogen-doped hollow carbon spheres not only ensure an ultra-high specific surface area for the accommodation of the Li2 O2 discharge products but also provide more reactive sites. CoO-Co3 O4 nanoparticles supported on the surface of the nitrogen-doped hollow carbon spheres can effectively catalyze the formation and decomposition of worm-like Li2 O2 . The batteries assembled with N-HC@CoO-Co3 O4 catalysts exhibit reduced overpotential, improved cycling performance, and high rate capability. Ultra-high discharge capacities of 24 265 mA h g −1 at a current density of 300 mA g −1 and 3622 mA h g −1 at a current density of 1000 mA g −1 are obtained. With a cutoff capacity of 500 mA h g −1, the battery with an N-HC@CoO-Co3 O4 electrode can reach more than 112 cycles. This research offers new insights into the design of heterostructured oxide catalysts for Li–O2 batteries.